Contextualizing ELT Materials through Local Folklore: A Case Study in a Multilingual Eastern Indonesian Classroom - Agus Setiawan; Mersi Axelina; La Sunra; Syarifuddin Dollah (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
In multilingual regions of Eastern Indonesia, English Language Teaching (ELT) materials that lack cultural relevance often fail to engage learners or reflect their linguistic realities. Local folklore offers a culturally grounded source for contextualizing ELT materials to enhance student learning and motivation. This study explores how local folklore can be integrated into ELT materials and investigates students’ multilingual practices and perceptions within a folklore-based classroom. A qualitative case study was conducted with one English teacher and thirty-two students in a multilingual secondary school. Data were collected through classroom observations, semi-structured interviews, and document analysis, and analyzed thematically. Findings show that folklore-based ELT materials enhance engagement, support comprehension through culturally familiar narratives, and promote active participation. Students naturally employed translanguaging strategies to negotiate meaning and strengthen English learning. The integration of folklore also reinforced cultural identity and pride among learners. Overall, contextualizing ELT materials through local folklore proved highly effective in multilingual classrooms, fostering inclusivity, meaningful learning, and cultural awareness. These results highlight the importance of incorporating local narratives into ELT curricula to promote culturally sustaining pedagogy in linguistically diverse settings.